A Systematic Literature Review on Project-Based Learning (PjBL) in Islamic Religious Education within the Independent Curriculum - Hasnida Hasnida; Muhammad Ali Akbar; Muh. Misbah; Meity H. Idris (Journal of Educational Studies, 2026)
The implementation of Islamic Religious Education (IRE) in schools continues to face persistent challenges, particularly in fostering students’ character internalization and overcoming passive, teacher-centered learning practices. These issues highlight the urgency of adopting more innovative and contextual learning models, such as Project-Based Learning (PjBL), within the Independent Curriculum framework. This study employs a library research method by systematically collecting and analyzing data from reputable academic databases, including Google Scholar, Scopus-indexed journals, and national accredited journals (SINTA). The selected literature was published between 2018 and 2024, resulting in a total of 25 relevant articles that were synthesized to examine the implementation of project-based IRE learning. The findings indicate that: (1) the project-based IRE learning model in the Independent Curriculum emphasizes experiential and contextual learning, where students engage in meaningful projects related to daily religious practices, such as observing community worship activities and conducting social campaigns, thereby enabling the practical application of Islamic values; (2) the implementation strategy involves structured project planning by teachers, continuous guidance throughout the learning process, and collaboration with external stakeholders, including religious leaders, while students actively participate both individually and collaboratively to construct their understanding; and (3) the urgency of this model lies in its capacity to enhance students’ independence, social competence, and Islamic character by facilitating the integration of religious teachings into real-life contexts, in alignment with the objectives of the Independent Curriculum.